2007
DOI: 10.1373/clinchem.2007.085688
|View full text |Cite
|
Sign up to set email alerts
|

Midregional Pro-A-Type Natriuretic Peptide and Carboxy-Terminal Provasopressin May Predict Prognosis in Community-Acquired Pneumonia

Abstract: Background: Markers to better assess severity of disease in patients with community-acquired pneumonia (CAP) would help improve medical care of this condition. The hemodynamic biomarkers carboxy-terminal provasopressin (CT-proAVP; copeptin) and midregional proatrial natriuretic peptide (MR-proANP) are increased under septic conditions, in which MR-proANP has been described as a prognostic predictor. We aimed to explore the diagnostic accuracy of MR-proANP and CT-proAVP to predict mortality in patients with CAP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
28
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 35 publications
4
28
1
Order By: Relevance
“…(28) Although our study involved patients with VAP, our results show some similarities to data presented in these studies of CAP. (27,28) In our study, the levels of procalcitonin, MR-proANP, and copeptin were also significantly higher in the nonsurvivors.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…(28) Although our study involved patients with VAP, our results show some similarities to data presented in these studies of CAP. (27,28) In our study, the levels of procalcitonin, MR-proANP, and copeptin were also significantly higher in the nonsurvivors.…”
Section: Discussionsupporting
confidence: 58%
“…(26) In another study, the PSI was found to correlate positively with MR-proANP level and copeptin level. (27) Those authors found that MR-proANP and copeptin levels were significantly higher in nonsurvivors than in survivors. In another study, involving 589 patients with proven CAP, the levels of MR-proANP, copeptin, CRP, and procalcitonin, as well as a mortality prediction score, were determined at admission.…”
Section: Discussionmentioning
confidence: 98%
“…5 Second, these scoring systems can underestimate the potential severity of CAP in young patients. 32 Of the many possible laboratory biomarkers, several serum markers, such as D-dimer, 33 cortisol, 34 B-type natriuretic peptide, 35 mid-regional pro-atrial natriuretic peptide, 36 and copeptin 37 levels, correlate well with the clinical outcomes of patients with CAP. However, these parameters are unsuitable for routine use in patients with CAP due to the cost of the assays or the retrospective nature of the results.…”
Section: Discussionmentioning
confidence: 99%
“…Whether CRP can be used for the etiological diagnosis of CAP has been extensively evaluated, but the results have been discordant [11,32,[34][35][36]. In the case of MR-proANP, there is no relationship with the etiology corroborating that MR-proANP levels reflect physiopathological dysfunction rather than etiology [16,37,38]. Regarding radiographic involvement, the PCT, CRP and neopterin levels were higher in patients with multilobar pneumonia, although in our previous experience, PCT correlated significantly with lobar involvement [6].…”
Section: Discussionmentioning
confidence: 99%